2020
DOI: 10.1177/0300060520964659
|View full text |Cite
|
Sign up to set email alerts
|

Potential interactions between pangenotypic direct-acting antivirals and concomitant cardiovascular therapies in patients with chronic hepatitis C virus infection

Abstract: Objective To identify potential drug interactions (DIs) between pangenotypic direct-acting antivirals (pDAAs) and concomitant cardiovascular (CV) therapies in patients with chronic hepatitis C (CHC). Methods A retrospective observational study was carried out. Patients ≥18 years of age diagnosed with CHC and treated with pDAAs during 2017 were included. Information was collected on concomitant CV therapies and potential DIs [ www.hep-druginteractions.org ]. The pDAAs analyzed were sofosbuvir/velpatasvir (SOF/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The concomitant treatments prescribed were in line with the results reported in a Spanish real-world study, in which the most consumed therapeutic groups belonged to the class of alimentary tract and metabolism (37.5%), cardiovascular system (37.5%), and nervous system (34.1%) [15][16][17]. In the Spanish cohort, GLE/PIB showed a higher prevalence of DDIs (17.8%), which was followed distantly by SOF/VEL (2.8%) [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The concomitant treatments prescribed were in line with the results reported in a Spanish real-world study, in which the most consumed therapeutic groups belonged to the class of alimentary tract and metabolism (37.5%), cardiovascular system (37.5%), and nervous system (34.1%) [15][16][17]. In the Spanish cohort, GLE/PIB showed a higher prevalence of DDIs (17.8%), which was followed distantly by SOF/VEL (2.8%) [15].…”
Section: Discussionsupporting
confidence: 85%
“…The same tendency was reported in the literature; Schulte et al [ 6 ] showed that contraindications due to DDIs interested 2% of SOF/VEL and 4% of GLE/PIB patients, while Sicras et al [ 15 ] observed that SOF/VEL presented a lower percentage of medication contraindicated compared to GLE/PIB (1.7% vs. 8.3%). There has been reported a greater number of contraindications with cardiovascular co-treatments associated to GLE/PIB vs. SOF/VEL in the Spanish cohort (12.8% GLE/PIB vs. 1.4%) [ 17 ]. These data are aligned with our results (2.7% GLE/PIB vs. few patients with SOF/VEL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the risk of bradycardia, amiodarone and sofosbuvir containing DAAs are contraindicated, and although the mechanism of this effect is unknown, the use of both drugs together should still be avoided . 23 Induction of CYP3A4 and P-glycoprotein by phenytoin and oxcarbazepine may signi cantly reduce serum concentrations of Elbasvir/grazoprevir and lead to loss of e cacy and potential treatment failure . 24,25 Therefore, pharmacists recommend suspending the use of drugs with contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies in real-life settings reported significant proportions of HCV patients with concomitant morbidities and related medications, mostly related to cardiovascular (CV) or central nervous system (CNS) conditions. 14–16 A previous real-world study by our group conducted in Italy on two cohorts of patients treated with sofosbuvir/velpatasvir (SOF/VEL) or glecaprevir/pibrentasvir (GLE/PIB) provided insights on their characteristics and DDI assessment based on the presence of at least one comedication. 16 The present analysis was aimed at an in-depth exploration of the potential impact of polypharmacy regimens and aging on the prevalence of multiple DDIs among patients treated with SOF/VEL or GLE/PIB in settings of daily clinical practice in Italy.…”
Section: Introductionmentioning
confidence: 99%